Development of Intelligent Gas Patrol Management System of Coal Mine - LIANG Peng; HUANG Jin-bo; WANG De-wei (Gong-kuang zidonghua, 2011)
To ensure accuracy and timeliness of gas monitoring data and realize safety early warning for gas, an intelligent gas patrol management system was developed. The system uses wireless technology and sensor technology, can real-timely monitor, display and voice prompt information of gas concentration, time, battery voltage and other information, and can upload patrol information to computer which can generate patrol routes or gas prediction curve for personnel of mine safety monitoring and management after the information are analyzed by system software. The industrial experiment result showed that the system can operate in reliable and has low failure rate.